PENGARUH VOLATILE FOOD TERHADAP INFLASI NUSA TENGGARA BARAT - Fadli, Fadli; Zaini, Anas (JURNAL AGRIMANSION, 2025)
The purpose of the study was to find volatile food commodities that affect regional inflation, both in the short run and long run. Using monthly time series data from January 2021 to December 2023, the data was then analyzed using the Error Correction Model (ECM). The results of the study concluded that there is a long-term equilibrium relationship between the inflation variable and the price of volatile foods with an adjustment speed of 33.8 percent per month when there is a shock that disrupts the equilibrium relationship. In addition, the effect of the price of rice and chicken eggs is positive and significant on inflation in both the short run and long run. Meanwhile, the price of cooking oil only has an effect in the long run, while the price of red chilies and granulated sugar has a positive effect in the short run.